Analysis of Supporting and Inhibiting Factors in The Implementation of The Pancasila Student Profile at State Elementary School 1 Damarguna - Meli Ameliya; Bagus Nurul Iman; Aiman Faiz (Journal of Educational Sciences, 2026)
This study aims to analyze the supporting and inhibiting factors in the implementation of the Pancasila Student Profile at Damarguna 1 Public Elementary School. The implementation of the Pancasila Student Profile is an important part of the Independent Curriculum as an effort to strengthen students' character through six main dimensions. This study used a descriptive qualitative approach with data collection techniques such as observation, interviews, and documentation. The research subjects were teachers and fourth-grade students. The results showed that supporting factors came from internal students such as enthusiasm and discipline, as well as external factors such as teacher role models and support for school policies. Inhibiting factors included limited teacher understanding, minimal project support facilities, and lack of parental involvement. These findings illustrate the importance of collaboration between schools, teachers, students, and parents in the successful implementation of the Pancasila Student Profile.